Spolsko občutljiv jezik v učbeniških besedilih za slovenščino - Ščuka, Nuša (Revija za elementarno izobraževanje, 2023)
In the discussion, we are dealing with a sample of textbooks for Slovene language as school subject in elementary school from the point of view of critical discourse analysis and the visual grammar of Kress and van Leeuwen (2020), focusing primarily on the use of gender sensitive language. Despite the fact that in the Slovene (school subject) the emphasis is on the verbal, school texts are multimodal. It means that they consist of verbal and pictorial codes, and make meaning in the interaction of both. The signs of both semiotic codes connect with each other and the reader of the school texts can easily undersand the meaning and the message. The analysis focuses on the concept of genders and the relationship between them.
Keywords: gender roles; gender sensitive language; Slovene language; slovenščina; spolne vloge; spolsko občutljiv jezik; stereotipi; stereotypes; textbook; učbeniška besedila